2019
DOI: 10.1021/acsabm.9b00628
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Spider Silk and Collagen-Based Nerve Guidance Conduits Support Neuronal Cell Differentiation and Functionality in Vitro

Abstract: Biomaterial scaffolds are under investigation as therapeutic tools to bridge nerve endings following traumatic peripheral nerve injury. The goal is to develop biocompatible nerve guidance conduits (NGCs) with internal guiding structures that promote longitudinally oriented cell migration and regeneration. In the present study, a nonwoven mesh (NWM) made of a recombinant spider silk protein was processed into a tubular structure, ensuring structural integrity of enclosed microfluidics-produced collagen fibers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Recombinant silk shall not only possess the unique material characteristics, but also show the same (or superior) effect on cells. Previous studies suggest different methods to analyze the behavior of cells to silk fibers 57,63,[65][66][67] or silk-based materials 68,69 in vitro. However, quantitative and qualitative read-outs designed to assess the biological response of cells to silk fibers concerning nerve tissue regeneration are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant silk shall not only possess the unique material characteristics, but also show the same (or superior) effect on cells. Previous studies suggest different methods to analyze the behavior of cells to silk fibers 57,63,[65][66][67] or silk-based materials 68,69 in vitro. However, quantitative and qualitative read-outs designed to assess the biological response of cells to silk fibers concerning nerve tissue regeneration are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Pawar et al [86,87] and Aigner et al [88] reported the development of NGCs using recombinant spider silk eADF4(C16) materials. Pawar et al [86,87] showed the use of fibers made of eADF4(C16) nonwoven-electrospun meshes filled with microfluidics-produced collagen fibers [87]. In this study, neuroblastoma X glioma hybrid cells NG108-15 were used and differentiated to study the effect of the individual components of the NGC on cell behavior.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
“…PC-12 cells cultured in these constructs showed differentiation and formation of aligned neurites within the microchannels, as well as along the aligned fibers of spider silk. Pawar et al [86,87] and Aigner et al [88] reported the development of NGCs using recombinant spider silk eADF4(C16) materials. Pawar et al [86,87] showed the use of fibers made of eADF4(C16) nonwoven-electrospun meshes filled with microfluidics-produced collagen fibers [87].…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheric tissues have shown excellent compatibility with cell growth and differentiation, the cells being able to achieve functional neuronal activity. Recombinant spider silk provided the anti-inflammatory barrier to the collagen compounds, while allowing the passage of nutrients and gas exchanges (Pawar et al 2019 ; Salehi et al 2020 ).…”
Section: High Value Applications For Electrospun Silkmentioning
confidence: 99%